2018
DOI: 10.1038/s41467-018-07160-7
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy high-hardness metal carbides discovered by entropy descriptors

Abstract: High-entropy materials have attracted considerable interest due to the combination of useful properties and promising applications. Predicting their formation remains the major hindrance to the discovery of new systems. Here we propose a descriptor—entropy forming ability—for addressing synthesizability from first principles. The formalism, based on the energy distribution spectrum of randomized calculations, captures the accessibility of equally-sampled states near the ground state and quantifies configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
496
5
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 736 publications
(571 citation statements)
references
References 69 publications
22
496
5
5
Order By: Relevance
“…The resulting ceramics had an average grain size of 16.4 ± 0.5 µm . Similarly, Sarker et al reported that (Hf, Zr, Ti, Ta, Nb)C ceramics produced by SPS at 2200°C using commercial carbide powders that were mixed by HEBM had an average grain size of more than 10 µm . In contrast, the (Hf, Zr, Ti, Ta, Nb)C ceramics in the present study had much finer grain sizes.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…The resulting ceramics had an average grain size of 16.4 ± 0.5 µm . Similarly, Sarker et al reported that (Hf, Zr, Ti, Ta, Nb)C ceramics produced by SPS at 2200°C using commercial carbide powders that were mixed by HEBM had an average grain size of more than 10 µm . In contrast, the (Hf, Zr, Ti, Ta, Nb)C ceramics in the present study had much finer grain sizes.…”
Section: Resultssupporting
confidence: 61%
“…Young's modulus increased from 405 ± 10 GPa to 452 ± 6 GPa as the densification temperature increased from 1750°C to 1900°C, which was attributed to the increase in the relative density as the densification temperature increased. (Figure ) Modulus values were higher than the value of 436 ± 30 GPa predicted using a volumetric rule of mixture (ROM) calculation and the modulus values of the nominally pure constituent carbides reported in previous studies . This has been attributed to the disorder associated with the multi‐metal composition .…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…As a member of high-entropy ceramics, the high-entropy metal carbides have recently aroused intensive research interests for their promising applications in various fields, such as aerospace, armors, and cutting tools. [8][9][10][11][12][13] The synthesis of high-entropy metal carbide powders is critical for implementing their extensive applications. To date, only two methods have been developed to synthesize high-entropy metal carbide powders.…”
Section: Introductionmentioning
confidence: 99%